2004
DOI: 10.1159/000078310
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia of the Parabrachial/Kölliker-Fuse Complex in Perinatal Death

Abstract: We report the first observation of perinatal death attributable to morphological alterations of the parabrachial/Kölliker-Fuse complex. In an infant, born at 41 weeks of gestation with severe signs of asphyxia and dead 20 h after delivery, we observed the presence of rare and immature neurons in the brain stem areas of both lateral and medial parabrachial nuclei and the absence of the characteristic neurons of the Kölliker-Fuse nucleus. Such hypoplasia was associated with severe hypoplasia of the arcuate nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…In our previous studies, we have reported the implication of the Kölliker-Fuse nucleus in the pathogenesis of SIDS and that its hypoplasia, like other brainstem alterations, is significantly associated with maternal smoking in pregnancy [5,8]. In this case however the mother admitted no history of cigarette smoking.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…In our previous studies, we have reported the implication of the Kölliker-Fuse nucleus in the pathogenesis of SIDS and that its hypoplasia, like other brainstem alterations, is significantly associated with maternal smoking in pregnancy [5,8]. In this case however the mother admitted no history of cigarette smoking.…”
mentioning
confidence: 57%
“…oscillations of pO 2 , pCO 2 and pH [5][6][7][8]. This activity is also sustained by the chemo receptor nuclei, to which the retrotrapezoid nucleus and the raphe obscurus nucleus belong [3,9].…”
mentioning
confidence: 99%
“…Another hypothesis is that the activity of the peripheral chemoreceptor, particularly the carotid body, increases dramatically as blood flow decreases [24], thereby overwhelming the inhibitory effects of the lateral pons. However, a recent study has demonstrated that in about a third of stillbirths there is congenital hypodevelopment of both the lung and the arcuate nucleus [25,26]. It was postulated that in these cases the arcuate nucleus hypoplasia could exert a negative effect on respiratory movements in utero and therefore on lung development.…”
Section: Chemoreception In the Fetusmentioning
confidence: 99%
“…A histopathological substrate should be searched for in a wide neuropathology field, including the brainstem nuclei, the cerebellum (cortex and deep nuclei), and the cardiac conduction system, subjected to strict autonomic control [2,10,11,23,26,28].…”
Section: Introductionmentioning
confidence: 99%